Assessing the healthfulness of pre-packaged beverages and investigating sugar thresholds for revising front-of-pack labels: a case study in Thailand - Nguyen Ngoc, Hung; Ditmetharoj, Mayuree; Rojroongwasinkul, Nipa; Winichagoon, Pattanee; Kriengsinyos, Wantanee (Frontiers in Nutrition, 2025)
Thailand's implementation of the “Healthier Choice” logo (THCL) as a front-of-pack nutritional labeling (FOPNL) scheme aims to promote healthier consumer food choices. In response, the beverage industry has increasingly replaced nutritive sweeteners (NS) with non-nutritive sweeteners (NNS) in their products. This study evaluates the energy and sugar content, sweetener usage, and overall healthfulness of pre-packaged beverages in Thai supermarkets, while also assessing their compliance with WHO “free sugar” consumption guidelines and exploring appropriate sugar thresholds for revising the THCL criteria. A cross-sectional audit was conducted in a major Bangkok supermarket between March and April 2022, collecting data on 881 pre-packaged beverages. To ensure a comprehensive evaluation, these beverages were further categorized based on product ingredients, THCL status, and sweetener type. Healthfulness was assessed using three validated nutrient profiling systems (NPS), and sugar threshold scenarios were evaluated using receiver operating characteristic analysis and area under the curve metrics. The median energy and sugar content per 100 ml were 37.9 kcal (21.9–52.2) and 5.00 g (2.0–7.8), respectively. Overall, pre-packaged beverages in Thai supermarkets were predominantly classified as “less healthy,” with 40.1% containing at least one NNS. Products carrying the THCL logo (27.7%) had lower energy and sugar content, indicating a “healthier” profile. However, these beverages also exhibited a higher prevalence of NNS compared to unlabeled products. Regardless of beverage type, consuming a typical bottle containing NS or a combination of NS and NNS in a single sitting often exceeded the WHO's recommended daily limit of 5% of total energy intake from free sugars. Thus, the study also proposes a phased approach to sugar reduction, initially lowering the sugar threshold to 5.0 g/100 ml, followed by a further reduction to 4.0 g/100 ml. In conclusion, the study underscores the widespread use of NNS in Thai pre-packaged beverages and identifies an overall “less healthy” nutritional profile across product categories. Reducing sugar content and implementing incremental sugar benchmarks in the THCL scheme are essential steps toward improving the healthfulness of pre-packaged beverages in Thailand and aligning these products more closely with WHO guidelines on sugar consumption.